Developing a Comprehensive Psychological Debriefing Program to Enhance the Well-Being of Police Personnel - Diaz Jr, Efren Dela Cruz; Villegas, June Rey A.; Narra, Donald B.; Relatorres, Queen Henyelour S. (Future Science / FSH-PH Publications, 2025)
This study conducted an assessment of the well-being of members of the Philippine National Police - City Intelligence Unit of the Cebu City Police Office for the period 2016 to 2021. A quantitative descriptive design was employed, utilizing the Ryff Scale 42 Items, Locus of Control, and General Self-Efficacy Scale to gather data. The majority of personnel were male with a baccalaureate degree, and variations were noted in the number of personnel assigned to each police station. The personnel exhibited relatively high scores on all autonomy sub-scales, while the majority demonstrated either low or moderate levels of self-efficacy. Using the Spearman's correlations, Well-being, locus of control, and self-efficacy were found to be statistically significant at the 0.05 level.